The Differential Sentencing of White-Collar Offenders in Ten Federal District Courts - Albonetti, Celesta (1980)
While sociologist have long debated the relationship between the status characteristics of criminal offenders and the sentences they receive, they have done so with data sets drawn from state courts whose prosecutorial resources are focused almost entirely on low status defendants. Qualitative and quantitative data analyzed in this paper are drawn from ten federal district courts whose statutes and resources provide greater potential for the prosecution of the white-collar crimes of higher status offenders. Three questions are addressed: (1) Are there substantial jurisdictional differences in the prosecution of white-collar cases? if so, (2) Are there corresponding jurisdictional differences in the sentencing of white-collar cases? and (3) Within jurisdictions, are there further differences in the factors that influence sentencing decisions in white-collar as compared to other kinds of cases? The data are analyzed from a perspective that emphasizes organizational considerations: we conceptualize the criminal justice process as a loosely coupled system and the use of prosecutorial resources as proactive and reactive. We argue that the expanded prosecution of white-collar persons for their white-collar crimes requires a proactive prosecutorial policy and a tightening of the coupling between plea negotiations and sentencing decisions in the prosecutorial and judicial subsystems. Our quantitative analysis reveals that one district follows a uniquely proactive pattern. As expected, this proactive district also exhibits a unique leniency in the sentencing of college educated white-collar criminals that is related to earlier plea and charging decisions. A rather different and unanticipated pattern of leniency is found in this district for less educated white-collar offenders. A conclusion of this study is that there may be an inverse relationship between the volume of white-collar prosecutions and the severity with which they are sentenced